Currarino syndrome and microcephaly due to a rare 7q36.2 microdeletion: a case report - Lucia Cococcioni; Susanna Paccagnini; Elena Pozzi; Luigina Spaccini; Elisa Cattaneo; Serena Redaelli; Francesca Crosti; Gian Vincenzo Zuccotti (BMC, 2018)
Abstract Background Currarino syndrome is a rare condition characterized by presacral mass, anorectal malformation and sacral dysgenesis. Case presentation We report the case of a child that presented chronic constipation, encopresis and mycrocephaly. The characteristics were initially compatible with a case of functional constipation and a therapy with polyethylene glycol was prescribed. After a year, because of poor response, a plain abdominal X-ray was performed, detecting sacrum abnormalities. Finally, a CGH-array analysis was performed and a form of Currarino Syndrome caused by a rare 7q36 microdeletion, was diagnosed. Conclusion Occult spinal dysraphism should be suspected in case of poor polyethylene glycol responder constipation, even when evident sacral abnormalities on the physical examination are not detected.